Six practical steps to support women farmers to drive climate resilience - Mishra, Avni; Gadeberg, Marianne (CGIAR GENDER Impact Platform, 2022)
Women and girls are burdened with a disproportionate share of the negative impacts of climate change, but they can also play key roles in climate change adaptation if solutions are designed to work for them. Women and men are affected by climate change impacts in different ways and have different opportunities and abilities to respond. Climate change adaptation and mitigation actions, policies and investments must take such differences into account to be successful. A climate change solution that does not work for women is not a climate change solution. In advance of COP27, we have identified six practical steps, based on past research from CGIAR and beyond, that governments, development partners and private sector investors must take to support women farmers to respond to climate change and drive resilience for everyone.